How to boost knowledge-spillover effects in disadvantaged regions? - Neves, M. F.; Ferreira, J. J.; Ferreira, F. (Knowledge Spillover-based Strategic Entrepreneurship – Routledge Frontiers of Business Management, 2016)
Over the past two decades or so, there has been considerable progress in the theory of knowledge spillover, which is also rooted on the foundations of entrepreneurship theory (Ghio, Guerini, Lehmann and Rossi-Lamastra, 2014). In this chapter, we seek to relate the phenomenon of knowledge spillover with the transfer of knowledge, generally considered the third component of Higher Education Institutions’ (HEIs) mission. First, HEIs have to obtain the competences necessary to transfer knowledge. Subsequently, in a second phase, the economic actors (EAs) have to deploy the capability to absorb the knowledge created, enabling the generation of innovative and marketable ideas that, when boosted by a favourable local context, can contribute towards regional development.